Combining hybrid Petri nets and hybrid automata. - Sava, A.T.
Hybrid systems have received much attention and a number of different models have been proposed in order to establish a mathematical framework which is able to handle both continuous and discrete aspects. Our research is focused on two models: hybrid automata and hybrid Petri nets (hybrid PNs). First, we deal with studying the hybrid PN functioning. An algorithm is proposed for constructing the hybrid automaton associated with a given hybrid PN. Next, we present the quantitative analysis of hybrid systems modeled by hybrid PN. The approach uses the reachability analysis of hybrid automaton to characterize the periodic functioning of a hybrid PN
Keywords: Hybrid Petri nets; Hybrid automata; Hybrid systems; Production control; Quantitative analysis; Reachability analysis